Model of Business Process Improvement in Organizations Based on the Business Process Improvement Approach - Yoppy Mirza Maulana (Journal of Advances in Information and Industrial Technology, 2023)
Business processes are key in managing activities and relationships between activities in an organization. However, managing business processes in organizations still has problems such as inefficiency and ineffectiveness. Therefore, good business process management is needed. Good business process management can be done by conducting business process analysis and modeling (BPAM). On this basis, a model of a business process improvement was created based on the Business Process Improvement approach. This model aims to improve business processes within a business activity and the relationships between business activities. This model produces stages that include 1) Determining the scope based on the value chain; 2) BPAM based on business process modeling notation; and 3) Business process improvement based on 12 tools fundamental and techniques of Integration, improvement, and replacement. Based on the results of applying this model, it can be used as a guide for organizations in making improvements to their business processes.